The impact of immersive virtual reality meditation for depression and anxiety among inpatients with major depressive and generalized anxiety disorders - Lee, Jungjoo; Kim, Junhyoung; Ory, Marcia G. (Frontiers in Psychology, 2024)
Background: Mindfulness-Based Cognitive Therapy (MBCT) is a nonpharmacological approach to alleviating depression and anxiety. While technology based MBCT is a standardized cost-effective approach, there have been concerns about its feasibility and effectiveness in clinical settings. Aims: The purpose of this study was to investigate the longitudinal relationship between improved emotional regulation resulting from participation in Immersive Virtual Reality Meditation (IVRM) and Major Depressive Disorder (MDD) and Generalized Anxiety Disorder (GAD) as monitored by electrocardiogram. Methods: This study was a longitudinal single-arm clinical trial in which the intervention was conducted three times a week for 10 weeks at a behavioral health unit in a community hospital (n = 26). We measured Coherence Achievement Score (CAS), depression, and anxiety. The relationships between CAS, anxiety, depression, and covariates were analyzed using a Generalized Estimated Equation (GEE). Results: The findings of our study provide evidence that the CAS scores indicative of emotional regulation function after IVRM participation were associated with a reduction in depression and anxiety. Conclusion: Among the many technology-based complementary health care interventions that are available to reduce depression and anxiety, IVRM program use increase emotional regulatory function and decrease depression and anxiety.